ANTIBACTERIAL POTENTIAL OF EGGPLANT FRUIT (Solanum melongena L) ETHANOL EXTRACT AGAINST Propionibacterium acnes BACTERIAL GROWTH - Irfan Zamzani; Islan Nor; Muhammad Raihan (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Acne is one of the skin problems that, without our realizing it, can reduce self-confidence, despair, and even depression among teenagers and young adults. The incidence of bacterial infections is increasing with the increasing cases of resistance of bacteria, such as Propionibacterium acnes, to the side effects of anti-acne drugs. Indonesia has many plants that are beneficial to humans and have properties for treating and improving health, one of which is the eggplant. The purpose of this study is to test whether eggplant has antibacterial activity against P. acnes. The eggplant was extracted using a maceration extraction method. For antibacterial activity, well diffusion agar was used with extract concentrations of 60%, 70%, 80%, and 90%. The inhibition zones of the ethanol extract of S. melongena at 60%, 70%, and 80% concentrations were 13,76 mm, 18,63 mm, and 20,79 mm, respectively, with the highest inhibition zone at 90% concentration at 20,64 mm. The ethanolic extract of S. melongena has a strong inhibitory effect on P. acnes. Â Keywords: antibacterial activity, Solanum melongena L, maceration, Propionibacterium acnes.